Symbolic or transformative? An assessment of gender equality spending in Mexico - Madrid Paredones, Rosa Marina (Revista Venezolana de Gerencia, 2025)
This article analyzes the evolution and distribution of gender-labeled public spending in Mexico through Annex 13 of the Federal Expenditure Budget from 2008 to 2024. The underlying problem lies in the disconnection between the increasing allocation of resources for gender equality and their limited impact on transforming structural inequalities. The general objective is to assess the extent to which Annex 13 resources have been directed toward programs with transformative potential for achieving substantive gender equality. Methodologically, the study applies a documentary and descriptive analysis using official sources, including approved and modified budgets, public accounts, and technical reports. The findings reveal a high concentration of funds in welfare-oriented programs, particularly in Branch 20 (Welfare), and underfunding of strategic initiatives in health, education, and gender-based violence prevention. The study concludes that, in its current form, budget labeling does not guarantee structural change toward gender equality, and normative and operational reforms are needed to enhance its effectiveness.